Shuji Ogino: a critical mass of pathological epidemiologists is needed for transdisciplinary studies - Li, Brad (Translational Gastroenterology and Hepatology; Vol 3 (November 2018): Translational Gastroenterology and Hepatology, 2018)
Molecular pathological epidemiology (MPE), which was first coined in 2010 (1,2), is an integrative field combining epidemiology and pathology, defined as “epidemiology of molecular pathology and heterogeneity of disease”. It utilizes molecular pathology to incorporate interpersonal heterogeneity of a disease process into epidemiology. While pathology and epidemiology both strive to elucidate etiology of disease, MPE aims at achieving this at molecular, individual and population levels (3).